German-language literature in Bulgaria since 2000. Statistics and some aspects of the reception - Vitcheva, Violeta (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
This article provides information on the trends in translating and publishing of German-language literature in Bulgaria between 2000 and 2022, based on several sources as well as on my own research. Then, using the reviews of three authors as an example, it points out some characteristics of the reception of German-language literature in Bulgaria, highlighting the contribution of Maya Razbojnikova-Frateva to its adequate placement in the Bulgarian cultural context after 2000.
Keywords: German-language literature; reception; Razbojnikova-Frateva; reviews; contemporary literature